Development of methodical fundamentals of formation of logistics system on the basis of sustainable development concept - Швец, Лілія Валентиновна (Technology audit and production reserves, 2016)
Today, when there is a change in the environment in the operation of enterprises, it is extremely important application and implementation of innovative management techniques. However, there is insufficient effectiveness of certain management decisions, and it is necessary to aim at effectiveness of business enterprise as a whole. It requires a detailed study, innovation management, including logistics based on traditional postulates and is the driving element in management of manufacturing processes and treatment resources. The key moment for enterprise management is construction of logistic system on the basis of sustainable development concept. Logistic approach provides a higher level of organization and management in terms of sustainable development, and the main task is to make it the main instrument of organization and management. Logistic system based on the principles of sustainable development of the enterprise is considered in this article in the light of the achievements of the strategic objectives of the enterprise and rationalization of its main operational processes with the allocation of general and logistic problems. An urgent character of the problem is the implementation of innovative methods for enterprise logistics management in terms of sustainable development.